Hurricane threat in Florida: examining household perceptions, beliefs, and actions. (3rd July 2017) - Basolo, Victoria; Steinberg, Laura J.; Gant, Stephen
ABSTRACT: Households in hurricane-prone regions respond to hurricane threat in numerous ways. Perceptions about their risk and other factors are thought to influence individuals' decisions to take protective actions for hurricanes. This research investigates the perceptions, behavioral intentions, and actual protective actions of a sample of residents in Miami-Dade County, Florida. We use unique data collected via a telephone survey to investigate a set of factors including risk perception, perceived local government readiness for a hurricane, past hurricane experience, hazard information exposure, and demographics, which have been posited to influence perceived hurricane preparedness, intent to evacuate under hurricane threat, and actual hurricane preparedness. The analytic results show that risk perception was positively associated with perceived preparedness, intent to evacuate, and one of the actual preparedness measures. Perceived local government readiness for a hurricane also was positively related to perceived preparedness and an actual protective measure. The results for other factors, including socio-demographics, varied by dependent variable. Following a report of the results, we discuss the research and policy implications of our findings.